Evaluation of the Competitive Factors Affecting Ticket Prices in Low-Cost Airlines - Mehmet Yaşar (İşletme Bilimi Dergisi)
Aim: This study was designed to determine the competitive elements that are thought to have an impact on the ticket prices of low-cost airlines.Method: Using ticket prices from routes in which Pegasus Airlines operates, a model was formed to examine the relationship between ticket prices and a variety of variables including the monthly frequency of the routes, the monthly available seats, the market share on the route, whether it is a monopoly on the route or not, the number of airlines operating on that route, whether there is another low-cost carrier on that route as well as the level of concentration on the route. Linear regression analysis and T-Test were used to test the model and reveal the levels of difference.Findings: The study found that market share, the number of flights on the route and route concentration values had a significant positive effect on the ticket prices. On the other hand, the presence of another low-cost airline on the route has a negative effect on ticket prices. In addition, ticket prices were found to be higher in monopoly markets and in markets with only one low-cost airline.